Responses of Heat Stress to Temperature and Humidity Changes Due to Anthropogenic Heating and Urban Expansion in South and North China - Yang, Shuai; Li, Shuwen; Chen, Bin; Xie, Zeming; Peng, Jing (Frontiers in Earth Science, 2021)
Due to global warming and human activities, heat stress (HS) has become a frequent extreme weather event around the world, especially in megacities. This study aims to quantify the responses of urban HS (UHS) to anthropogenic heating (AH) emission and increasing city size based on numerical simulation. Then we estimate the primary driving factor to extreme heat stress (EHS) occurrence by weighting temperature change and humidity change more heavily. Analyses show both components of AH, anthropogenic sensible/latent heating (ASH/ALH), could intensify HS, by heating and humidifying roles respectively. Together, they produce maximal increment of moist entropy (an effective HS metric) about 1.5K over high-density urban, meaning the total AH release could aggravate UHS drastically. Among them, ALH effect accounts for a larger proportion, dominant of the HS spatial pattern. HS change exhibits prominent diurnal variation feature, associated with the diurnal cycles of ASH and ALH, which is more evidently in north than in south. And sprinkling water on roads or gardens over north cities in the afternoon might slightly alleviate HS by ALH effect, but it does not work for south cities. As city expands dramatically in the future, HS coverage increases. UHS experiences enhancements in north, with peak of about 4K, mostly driven by urban heat island. However, UHS has smaller peak (~2K) in south, and maintains less variation in intensity because of nearly synchronously growing out-of-phase contributions of temperature rise and moisture depict to UHS. Therefore, it is more prone to severe UHS risk if we build up megacities in north in the future. For the EHS, about one-third urban region might be hit by EHS in the future, with wider scope of influence in south but larger extremum in north. Furthermore, the larger the cities are, changes in the very warmest EHS events are more associated with large humidity change responses, irrespective of north or south cities. Therefore, constraining the occurrence probability and regional distribution of EHS events largely comes down to constraining the humidity change associated with these events, particularly in megalopolis or city cluster. These results serve for effective urban planning and future decision making.